A comparison with natural particles reveals a small specific effect of PVC microplastics on mussel performance. (November 2020) - Yap, Vincent H.S.; Chase, Zanna; Wright, Jeffrey T.; Hurd, Catriona L.; Lavers, Jennifer L.; Lenz, Mark
Abstract: Effects of microplastics on marine taxa have become a focal point in marine experimental biology. Almost all studies so far, however, assessed the influence of microplastics on animals only in relation to a zero-particle group. Documented microplastic impacts may thus be overestimated, since many marine species also experience natural suspended solids as a stressor. Here, we compared the effects of polyvinyl chloride (PVC) and red clay (mean for both particles: ~12–14 μm) on the Mediterranean mussel Mytilus galloprovincialis across three particle concentrations (1.5, 15, 150 mg l −1 ). Exposure to PVC for 35 days lowered mussel body condition index by 14% in relation to clay, but no difference in byssus production, respiration and survival rates emerged between the two particle types. This suggests that the effects of synthetic particles on filter feeders may emulate those of natural suspended solids, and highlights the importance of including natural particles in microplastic exposure studies. Highlights: Mussel BCI was 14% lower after exposure to PVC particles in comparison to red clay. Byssus production, respiration and survival did not differ between particle types. Mussels suffered little from the five-week particle exposure up to 150 mg l −1 .